2008
DOI: 10.1016/j.jad.2007.12.229
|View full text |Cite
|
Sign up to set email alerts
|

Differential interactions between comorbid anxiety disorders and substance use disorder in rapid cycling bipolar I or II disorder

Abstract: Objective-Anxiety disorders (AD) and substance use disorders (SUD) commonly co-occur with bipolar disorder. This study was undertaken to assess AD-SUD-bipolar subtype interactions.Methods-Extensive clinical interview and MINI were used to ascertain DSM-IV diagnoses of rapid cycling bipolar I (RCBPDI) or II (RCBPDII) disorder, SUDs, and ADs including generalized anxiety disorder (GAD), panic disorder (PD), and obsessive-compulsive disorder (OCD). Data at the initial assessment of four studies was used to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…The ECA study data showed that patients with bipolar I disorder had higher rates of SUD than those with bipolar II disorder. 7 Our previous analysis 27 in a larger sample of patients with rapid-cycling bipolar disorder also showed that patients with rapid-cycling bipolar I disorder had significantly higher rates of SUDs than those with rapid-cycling bipolar II disorder. Higher rates of comorbid SUDs in patients with bipolar I disorder (42%–78%) compared to those with bipolar II disorder (17%–48%) has been reported in other studies.…”
Section: Discussionmentioning
confidence: 91%
“…The ECA study data showed that patients with bipolar I disorder had higher rates of SUD than those with bipolar II disorder. 7 Our previous analysis 27 in a larger sample of patients with rapid-cycling bipolar disorder also showed that patients with rapid-cycling bipolar I disorder had significantly higher rates of SUDs than those with rapid-cycling bipolar II disorder. Higher rates of comorbid SUDs in patients with bipolar I disorder (42%–78%) compared to those with bipolar II disorder (17%–48%) has been reported in other studies.…”
Section: Discussionmentioning
confidence: 91%
“…A “recent” SUD was defined as having a diagnosis of substance dependence and continuing to meet abuse or dependence criteria for a substance(s) in the last 6 months at the time of initial assessment or having a diagnosis of substance abuse and continuing to abuse a substance(s) in the previous 3–6 months. The study design, inclusion and exclusion criteria, mood state at study entry, and the stage of each study at the time of this analysis are summarized elsewhere 19,23 …”
Section: Methodsmentioning
confidence: 99%
“…Previously, we found that the increased rates of GAD and panic disorder, but not obsessive compulsive disorder (OCD), only occurred in patients with rapid‐cycling bipolar I disorder (RCBDI) and co‐occurring SUDs, not in those with RCBDI without a history of SUDs or in those with rapid‐cycling bipolar II disorder (RCBDII) 19 . However, among patients with RCBD and a recent history of SUDs, patients with either subtype had more similarities than differences in the rates of historical clinical variables, the number of SUDs, scores on the addiction severity index, and scores of global assessment scale 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of comorbid anxiety with suicidality is questionable (Slama et al 2004 ). Probably it is more frequent in BD-II than in BD-I patients (Dittmann et al 2002 ), although rapid cycling and substance abuse might reverse this and dramatically increase anxiety rates in BD-I (Gao et al 2008 ).…”
Section: Comorbid Anxietymentioning
confidence: 99%